Pancasila as the Basis for Legal Development in Indonesia - Sajid, Daffa Alim (Jurnal Scientia Indonesia, 2018)
As determined by the formation of the state that the primary goal is the formulation of Pancasila as the foundation of the Republic Indonesia. Therefore, the principal function Pancasila as the state is based on MPRS No.XX/MPRS/1966 (MPR No.V/MPR/1973 jo, jo No.IX/MPR/1978 MPR), which explained that Pancasila as the source from all source or sources of law rule of law in Indonesia, which is essentially a way of life, consciousness and ideals of the legal and moral ideals which include mystic atmosphere and character of Indonesian nation. And then about Pancasila as the source of all sources of law are explained again in MPR No.III/MPR/2000 about the source of law and order legislation in Article 1 paragraph (3) which states that "the basic source of national law is Pancasila. With the formation of Act No.10 of 2004 on the Formation of legislation, as enshrined in Article 2 of Law 10 of 2004 which states that "Pancasila is the source of all sources of state law," firmly stated Pancasila as the source of all sources law as follows: "the position of Pancasila as the source of all sources of state law is in accordance with the Preamble of the 1945 Constitution that puts Pancasila as the state ideology and at the same philosophical foundation of the nation, so any substance laws and regulations not be contadiction with the values contained in Pancasila.